Multiple-criteria decision analysis to promote recycling activities at different stages of urbanization. (20th November 2016) - Challcharoenwattana, Amornchai; Pharino, Chanathip
Abstract: This study takes a holistic approach to provide decision support for selecting recycling practices that are suitable for urban settlement without mandatory recycling, such as Thailand. The study employed analytic hierarchical process (AHP) to nominate the most optimal informal recycling modes for municipal solid waste (MSW), namely, itinerant recyclable buying (IRB), recycling center buying (RCB), and donation to charity (DOC). Studies of MSW characteristic at landfills, willingness to pay and recycling attitudes using questionnaire surveys (n = 1063), and reviews of existing MSW management system were carried out in three urban settlements, classified as peri-urban (PS), urban (US), and metropolis (MS), that differ in size and administrative capacity in Thailand. Findings from the above studies were then used for creating AHP's evaluating criteria as willingness to recycle (WTR), potential reduction of landfill cost (C-MSW), and additional willingness to pay for the implementation of a recycling system (A-WTP). For WTR, we found that recycling modes with monetary return, IRB and RCB, remained the preferred venue of recycling as they consistently ranked higher than non-monetary return option (DNO) in all sites. For C-MSW, the result indicated that the choice of IRB were able to save the cost of waste management as IRB tended to induce highest diversion rates in all three sites. For A-WTP, the study found that respondents who opted to recycle via IRB were often commended the highest WTP compared to other mode of recycling in all sites. The final AHP scores (PS:IRB = 0.75, RCB = 0.13; US:IRB = 0.56; RCB = 0.35; MS: IRB = 0.65; RCB = 0.13) for all sites indicated that IRB was the most optimal option to promote recycling. Therefore, itinerant recyclable buying is a recommended option for all urban settlements as an effective, informal MSW collection activity. Graphical abstract: Highlights: Itinerant recyclable buying was the optimal alternative for all study sites. MSW compositions don't vary with urbanization except % of paper and plastic. Incurring a high MSW servicing fee without a recycling system may be ineffective. Impact of socio-economic factors vary at different levels of urbanization.